(untitled) (Global Journal of Human-Social Science, 2013)
The current treatise is an attempt to unveil the phonological nature of sound change and to trace the extent to which the sound change is patterned and functioned via the historical and contextual developments of Basrah Arabic. Language change is generally attributed to three major factors: "syntagmatic change", "paradigmatic or associative change" and "social change". The facts and factors that underline the sound change can possibly be accounted for as to which theories have been propped. The most prominent of which are performance theories and competence theories.